2018
DOI: 10.1039/c8cp03843k
|View full text |Cite
|
Sign up to set email alerts
|

From strong to weak NF bonds: on the design of a new class of fluorinating agents

Abstract: A set of 50 molecules with NF bonds was investigated to determine the factors that influence the strength of a NF bond, with the aim of designing a new class of fluorinating agents. The intrinsic bond strength of the NF bonds was used as bond strength measure, derived from local stretching NF force constants obtained at the CCSD(T)/aug-cc-pVTZ and ωB97XD/aug-cc-pVTZ levels of theory. The investigation showed that the NF bond is a tunable covalent bond, with bond strength orders ranging from 2.5 (very strong) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 151 publications
2
45
0
Order By: Relevance
“…Another important feature of L-modes is the direct relationship between the local stretching force constant (k a ) of a chemical bond and its intrinsic strength [113]. This has enhanced our knowledge about chemical bonding and the often overlooked, but highly important weak intermolecular interactions, providing a wealth of new insight into: (i) covalent bonding [113], stretching from peculiar cases of reversed bond length-bond strength relationships [114,115], to a new design recipe for fluorinating agents [116]; (ii) weak chemical interactions including hydrogen bonding [117,118], XB [35,41,42], pnicogen bonding [43], chalcogen bonding [50], weak interactions in gold clusters [119], as well as non-classical hydrogen bonds in boron-hydrogen • • • π interactions [120,121]. In addition, new electronic parameters and rules were derived [122][123][124].…”
Section: Methodsmentioning
confidence: 99%
“…Another important feature of L-modes is the direct relationship between the local stretching force constant (k a ) of a chemical bond and its intrinsic strength [113]. This has enhanced our knowledge about chemical bonding and the often overlooked, but highly important weak intermolecular interactions, providing a wealth of new insight into: (i) covalent bonding [113], stretching from peculiar cases of reversed bond length-bond strength relationships [114,115], to a new design recipe for fluorinating agents [116]; (ii) weak chemical interactions including hydrogen bonding [117,118], XB [35,41,42], pnicogen bonding [43], chalcogen bonding [50], weak interactions in gold clusters [119], as well as non-classical hydrogen bonds in boron-hydrogen • • • π interactions [120,121]. In addition, new electronic parameters and rules were derived [122][123][124].…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the local stretching force constant k a is a superior bond strength measure compared to the often used bond dissociation energies (BDE) and bond dissociation enthalpies (BDH) as they contain cumulative effects of geometry relaxation, multiple bonding interactions, and also electronic density reorganizations of the dissociated fragments . Local stretching force constants k a have been successfully used to determine the intrinsic bond strength of covalent bonds such as: CC bonds, NN bonds, NF bonds, CO bonds, and CX (X=F, Cl, Br, I) bonds, and weak chemical interactions such as: hydrogen bonding, halogen bonding, pnicogen bonding, chalcogen bonding, tetrel bonding, and recently BH···π interactions …”
Section: Introductionmentioning
confidence: 99%
“…[25,[73][74][75] It has been shown that the local stretching force constant k a is a superior bond strength measure compared to the often used bond dissociation energies (BDE) and bond dissociation enthalpies (BDH) as they contain cumulative effects of geometry relaxation, multiple bonding interactions, and also electronic density reorganizations of the dissociated fragments. [73,76,77] Local stretching force constants k a have been successfully used to determine the intrinsic bond strength of covalent bonds such as: CC bonds, [74,75,78,79] NN bonds, [80] NF bonds, [81] CO bonds, [82] and CX (X = F, Cl, Br, I) bonds, [83][84][85][86] and weak chemical interactions such as: hydrogen bonding, [87][88][89][90] halogen bonding, [91][92][93] pnicogen bonding, [94][95][96] chalcogen bonding, [73,77] tetrel bonding, [97] and recently BH � � � p interactions. [16,17] The main objectives of this paper are: (i) to evaluate the nature of the BÀ B, BÀ H b , and BÀ H t bonds; (ii) to evaluate why intermediate species may or may not facilitate the reversibility reactions in the perspective of thermodynamics and intrinsic bond strength; (iii) to provide a new tool to characterize new (potential) intermediates and their role for the reversibility of the hydrogenation/dehydrogenation reactions; and (iv) to give guidelines whether intermediates may be stable enough to be isolated.…”
Section: Introductionmentioning
confidence: 99%
“…The local mode analysis has been successfully applied to characterize covalent bonds [63,65,108,[116][117][118][119] and weak chemical interactions such as halogen [15,16,80,120], chalcogen [17,102,121], pnicogen [122][123][124], and tetrel interactions [64] as well as H-bonding [18,[125][126][127][128][129] and BH• • • π interactions [130,131]. A new metal-ligand electronic parameter (MLEP) was derived as quantitative measure of the intrinsic strength of metal-ligand bonding [129,[132][133][134][135].…”
Section: The Theory Of Local Vibrational Modesmentioning
confidence: 99%
“…Therefore, the BDE is not a suitable measure of the intrinsic strength of a chemical bond as it is strongly affected in non-predictable ways by the changes of the dissociation fragments. Accordingly, its use has led in many cases to a misjudgment of bond strength [16,45,[61][62][63][64]. Also, the bond length is not a qualified bond strength descriptor.…”
Section: Introductionmentioning
confidence: 99%